Identification and In Silico Analysis of Anti Inflammation and Anti Oxidant Potentials of Polyphenol Compounds in Methanol Extract of Tamarindus indica Seeds - Muhammad Ihwan Narwanto; Masruroh Rahayu; Setyawati Soeharto; Nurdiana Nurdiana; Moch. Aris Widodo (Journal of Agromedicine and Medical Sciences, 2018)
ABSTRACT Indonesia has abundant stock of Tamarindus indica seeds, but it is not yet utilized maximally, especially in medical field. Tamarindus indica seeds have high content of polyphenols compound. No reseacrh is supported by in silico data on polyphenol compound in Tamarindus indica seeds extract. Polyphenols compound can be utilized as a neuroprotective agent. This research aims to measure polyphenols concentration in methanol Tamarindus indica seeds extract and determine the anti inflammation and antioxidant potential of each polyphenol compound in methanol Tamarindus indica seeds extract by in silico method. The extraction of Tamarindus seeds used maceration method and methanol as solvent. Identification and measurement of polyphenols compound applied HLPC-MS. PyMol and Pyrx tools were used for in silico analysis. Extract recidu was obtained from methanol Tamarindus indica seeds as much as 12%w/v. HPLC-MS anaysis mentioned that levels of procyanidin B2, myricentin and caffeic acid were respectively 38.850 mg/kg, 5.845 mg/kg and 260 mg/kg. The highest anti inflammatory potential was owned by myricentin than caffeic acid, while the lowest potential in procyanidin B2. Furthermore, the highest antioxidant potential was sequentially in myricentin, procyanidin B2 and caffeic acid. It is very possible to utilize methanol Tamarindus indica seeds extract for preventing neurodegenerative diseases since its pathogenesis involves inflammatory and stress oxidative process. Keywords : Tamarindus indica, myricetin, procyanidin B2, caffeic acid, anti inflammatory, antioxidant